Evaluation of Grain Yield and Yield Stability in Rapeseed (Brassica Napus) Mutant Lines Using GGE Biplot - B Naserian Khiabani; B Alizadeh (مجله علوم و فنون هسته‌ای, 2018)
In order to evaluate the mutant lines derived from irradiation of oilseed rape cultivar RGS003 using gamma-ray, this study was carried out during two growing seasons from 2011 to 2013, at the experimental fields in the Nuclear Agricultural Research School. The experimental design was a randomized complete block design with three replications. Significant differences were observed between mutant genotypes and cultivars for grain yield during two years of the experiment. Interaction of year × genotype (GE) showed a significant difference. Identification and selection of mutant lines, especially in the quantitative traits due to the interaction of genotype and environmental effects, is very important and complicated. The biplot method is an effective approach for the selection of mutant lines, based on the traits and yield stability over the time. The aim of this research was selection of the superior mutant lines from of 32 mutants, using the GGE biplot method. The mutant lines RG16, RG14 and RG31 showed high and stable grain yields compare to other mutant lines and cultivars. According to our results, mutation breeding can be used effectively in oil seed rape improvement.